Exploring Sixth Graders' Interest in English Language Learning : A Descriptive Study in Ngabang - Aswan Aswan; Aunurrahman Aunurrahman; Maliqul Hafis (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study aimed to investigate the level of students' interest in learning English at a public primary school in Ngabang in the academic year 2025/2026. This research employed a quantitative descriptive survey design. The population of this study consisted of sixth-grade students. The sample was selected using a total sampling technique, involving all students as participants. The instrument used in this study was a closed-ended questionnaire consisting of 14 items. After conducting a pilot test, two items were found to be invalid and excluded. This resulted in 12 valid items used in the main data collection. The data were analyzed using descriptive statistics, including mean scores and percentages. The findings showed that the overall mean score of students' interest was 3.44, which was categorized as "Very High". Based on the two measured aspects, namely knowledge of English and need for English, the results indicated that students possessed adequate basic knowledge and strong curiosity toward learning English. However, their exposure to the language outside the classroom was relatively limited. Furthermore, students demonstrated a high perception of the importance of English for their future, including education, communication, and career opportunities. In conclusion, students at a public primary school in Ngabang exhibited a very high level of interest in learning English. This finding suggests that students are psychologically ready to learn English despite limited(Schiefele, 1991) external exposure. Therefore, English teachers and school administrators should provide more interactive learning activities and increase exposure to support the learning process.